Potencial de uso de partículas biodegradáveis de pectina, quitosana e vinhaça como fertilizante agrícola - Cerri, Bianca Carreiro (Universidade Federal de São Carlos, 2019)
Technologies able to control or hinder the release of nutrients from fertilizers have been studied in order to improve agricultural systems with minimum environmental impact. In this context, biodegradable polymers extracted from renewable sources, such as pectin and chitosan, have been considered as alternative polymeric matrices for the development of slow/controlled release systems with a focus on agriculture. Previous studies of our research group have focused on the development of pectin and chitosan particles using vinasse (the main wastewater from the ethanol production) as solvent, showing promising results regarding functional and chemical properties for fertilizer application. This work evaluated the potential use of particles based on these agroindustrial by-products as alternative fertilizers for soil applications. Pectin (Pec_V) and chitosan (Quit_V) particles with vinasse were obtained by dripping the biopolymeric solutions in crosslinker solutions. Particles with water as solvent were produced as control. Physical, chemical and physico-chemical properties of the particles, as well as, the biodegradation in soil, the release of nutrients in water and water retention behavior (in clay and sandy soil) were evaluated. The addition of vinasse conferred greater stability to the pectin gel compared to the formulation with water, showing a positive impact on particles properties. Particles had spherical shape, and granulometric specification of coarse grained. Compared to Quit_V, Pec_V were more soluble, showed higher swelling degree and lower compression force. Pec_V and Quit_V exhibit biodegradation degree of 65.1% and 68.0%, respectively, after 113 days of contact with soil. Water evaporation rates were lower for sandy soil containing Quit_V and Pec_V, compared to control soil (without particles), indicating good perspectives for the use of particles in drought-prone regions. According to the Brazilian legislation, Pec_V can be classified as mixed organic fertilizer class A after pH adjustment to 6.0. Quit_V were classified as organomineral fertilizer class A, added with Ca, S, Cu, Fe, Mn and Zn. Particles with vinasse showed potential to be applied as fertilizer in agriculture, allowing the recycling of nutrients from vinasse to the soil and, above all, represent a novel alternative for the use of this expressive wastewater from the sugar and alcohol industry.
Potential for the use of biodegradable particles of pectin, chitosan and vinasse as agricultural fertilizer
Keywords: Subprodutos agroindustriais; Biopolímeros; Fertilizantes de liberação lenta; Agroindustrial byproducts; Biopolymers; Slow release fertilizer; CIENCIAS AGRARIAS